MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA - Iis Noviyanti Iis Noviyanti (KREATIF : Jurnal Ilmiah Prodi Manajemen Universitas Pamulang, 2016)
The problems that exist at the University of Pamulang is that about studentachievement , which is influenced by motivation with the understanding that motivation carried out by teachers do not actively implemented with the understanding that the motivation to do still lacking. This can be evidenced by the negligence committed by students. Student disciplinary action is one of the symptoms caused by the lack of motivation to the functioning properly, which in turn would hinder achieving goals. The purpose of this study was to determine:1. To find out how student motivation.2. To find out how the students' achievement.3. To find out how the relationship between motivation and academic achievement of students. The research method using descriptive research with survey techniques. The analytical approach used in this study is the use of a quantitative approach, the type of statistics used in the study is a nonparametric statistics. These samples included 56 respondents. With the good motivation, it can improve learning achievement. The learning achievement will have a positive impact on the achievements of the college, for that a college should strive to improve learning achievement in various ways. A college in thiscase if the Pamulang University has students with good learning performance, it will bring the good name of the college. From analysis to determine the relationship between two variables, it is known from the correlation coefficient calculation, based on the interpretation of the correlation coefficient according Sugiyono (2007: 187) a correlation value of 0.753 indicates a strong relationship between the level of motivation and academic achievement. Of calculating the coefficient of determination is known that increased learning achievement is influenced by the motivation of 56.70% and the remaining 43.30% is determined by other factors not examined in the study. In the hypothesis testobtained t count> t table, which means that the hypothesis H1 is accepted.